Race and Territory in the Pan-Africanist Thought of Kwame Nkrumah - Osemwengie, Ikonnaya Okomba (NIU Journal of Humanities, 2026)
This study examines the relationship between race and territory in Pan-Africanist thought, with a particular focus on the ideas of Kwame Nkrumah. It aims to clarify whether Pan-Africanism developed as a single evolving tradition or as distinct but overlapping frameworks shaped by different historical conditions. The study adopts a qualitative and interpretive methodology, relying on textual analysis of Nkrumah’s major writings and speeches, alongside a critical engagement with existing scholarship on Pan-Africanism. The findings show that Pan-Africanism manifested in both racial and territorial forms. While its early development in the diaspora was grounded in racial solidarity and the struggle against discrimination, its later articulation in Africa responded to the demands of colonial rule, political independence, and state formation. Rather than representing a simple transition, these forms coexisted and addressed different concerns. Nkrumah’s thought illustrates this dynamic, as he rejected racialism as a guiding principle while advancing a territorially grounded vision of African unity and political organization. The study contributes to ongoing debates by offering a clearer distinction between racial and territorial Pan-Africanism and by situating Nkrumah within this framework. It is relevant to scholarship on African political thought, decolonization, and the intellectual history of Pan-Africanism. Keywords: Pan-Africanist thought, Kwame Nkrumah, race and territory, anti-racialism, continentalism, African unity, political organization